Obstacle Detection System for Railways using IoT Sensors - Mohamad, Khairul Anuar; Aziz, Ahmad Akmal; Alias, Afishah (Evolution in Electrical and Electronic Engineering, 2020)
Accidents that involve trains on the railway is a crucial issue and need to be avoided. Detecting obstacles is vitally essential nearby and on the railway to ensure the smooth running of the trains. Thus, Keretapi Tanah Melayu Berhad (KTMB) has provided a safety system by relying on visual inspection to monitor the railway. This project aims to provide an alternative precaution measurement that can aid the railway’s existing safety system. The project uses two mediums to collect and monitor data about the detecting obstacles nearby and on the railway. The first medium used in this project is the IoT-based system by using FavorIoT as a cloud server platform at the prototype for storing and monitoring data about the distance between obstacles and the prototype. Another medium used is a radar display by using Processing Software to display the distance between obstacles and the device in the range between 0 – 40 cm. Three ultrasonic sensors are used to provide a dependable notification system to detect the obstacles nearby and on the railway, which placed at the front, right and left sides. Arduino IDE is used to program Arduino NodeMCU, which acts as the brain of the system. The system commands the three ultrasonic sensors to detect the distance between obstacles and the device and send the data via Wifi to the FavorIoT as a cloud server. The prototype managed to collect data in a data stream of FavorIoT and monitor data in the radar display form.